A nano calcium fluoride modified thermoplastic polyurethane battery separator and a preparation method thereof

CN122889950APending Publication Date: 2026-10-09SHENZHEN ALDEAN TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611280900.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-23
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,上述方法仍存在局限性:电解液添加剂会增加体系复杂度且可能带来副反应,正极包覆工艺复杂且增加非活性质量,隔膜涂覆往往需要额外的粘结剂和复杂的涂布工艺

Benefits of technology

[0021](1)本发明通过在TPU基体中引入纳米氟化钙,利用其高比表面积和表面钙离子对氟离子的静电吸附作用,有效捕获电解液中的游离氟离子,从源头上抑制HF的生成与腐蚀作用,延长电池的使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889950A_ABST
    Figure CN122889950A_ABST
Patent Text Reader

Abstract

The application discloses a kind of nano calcium fluoride modified thermoplastic polyurethane battery separators and preparation method thereof.The battery separator includes thermoplastic polyurethane and nano calcium fluoride uniformly dispersed in thermoplastic polyurethane matrix, the particle size of nano calcium fluoride is 10-500nm, and the addition amount is 0.5-20wt% based on the weight of thermoplastic polyurethane.The application uniformly disperses nano calcium fluoride in thermoplastic polyurethane matrix, utilizes its high specific surface area to adsorb free fluoride ions in electrolyte, inhibits the generation and corrosion of hydrofluoric acid;Nano calcium fluoride can react with lithium carbonate in electrolyte to generate lithium fluoride and calcium carbonate functional protective layer, optimize solid electrolyte interface composition, inhibit lithium dendrite growth;At the same time, the mechanical properties and thermal stability of the separator are enhanced, and lithium ion conduction is promoted.The preparation process of the application is simple, suitable for large-scale production, and can improve the cycle stability and safety performance of lithium ion battery and lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, specifically to a battery separator and its preparation method, and more particularly to a thermoplastic polyurethane (TPU) battery separator containing nano-calcium fluoride (CaF2) and its preparation method and application. Background Technology

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and environmental friendliness. The battery separator, a key component of lithium-ion batteries, is located between the positive and negative electrodes. Its main function is to isolate the positive and negative electrodes to prevent short circuits, while allowing lithium ions to pass freely in the electrolyte.

[0003] Currently, commercially available lithium-ion battery separators are mainly made of polyolefin microporous membranes (such as polyethylene (PE), polypropylene (PP), and their composite membranes). However, polyolefin separators have problems such as poor electrolyte wettability, insufficient thermal stability (easily shrinking at high temperatures), and limited mechanical strength, making it difficult to meet the growing demands of high-energy-density batteries for safety and cycle life.

[0004] Thermoplastic polyurethane (TPU) has attracted increasing attention in the field of battery separators in recent years due to its excellent flexibility, good mechanical properties, good compatibility with carbonate electrolytes, and tunable microporous structure. However, single-layer TPU separators still have problems such as low ionic conductivity and the need for further improvement in thermal stability.

[0005] Lithium-ion battery electrolytes typically consist of carbonate-based organic solvents and lithium salts such as lithium hexafluorophosphate (LiPF6). LiPF6 is extremely sensitive to moisture; even in highly purified battery-grade electrolytes, trace amounts of water (approximately 10-25 ppm) are unavoidable. This leads to the decomposition of LiPF6 and the formation of hydrofluoric acid (HF). HF is a highly corrosive acid that attacks the positive electrode material and dissolves transition metal ions. These dissolved metal ions migrate to the negative electrode surface and deposit, causing negative electrode failure. HF also attacks and dissolves the SEI film components on the negative electrode surface, exposing fresh electrode surfaces to the electrolyte and exacerbating its continued decomposition. The presence of HF has been identified as one of the main causes of electrolyte decomposition and shortened battery life.

[0006] To suppress the damage of HF to battery performance, existing technologies mainly adopt the following strategies: (1) adding alkaline additives to the electrolyte to chemically consume HF; (2) coating the surface of the cathode material; and (3) coating the separator with a functional coating. However, the above methods still have limitations: electrolyte additives increase the complexity of the system and may bring side reactions; cathode coating process is complicated and increases inactive mass; and separator coating often requires additional binders and complicated coating processes.

[0007] In recent years, research has explored the application of calcium fluoride (CaF2) in battery separators. Chinese patent CN120767538A discloses a method for preparing a composite separator, which involves uniformly dispersing calcium fluoride powder and polyvinylidene fluoride (PVDF) powder in a specific ratio in NMP solvent to obtain a coating. This coating is then applied to the surface of a substrate separator. Calcium fluoride replaces lithium carbonate (Li2CO3) generated from the decomposition of carbonate electrolyte, in situ generating lithium fluoride (LiF) and calcium carbonate (CaCO3) to optimize the composition and stability of the solid electrolyte interface (SEI). However, the existing technology still has the following shortcomings: the application of calcium fluoride in separators is mainly limited to the coating layer, and the substrate is mostly polyolefin separators such as PE and PP, lacking an integrated solution for uniformly dispersing nano-calcium fluoride as a filler in a TPU matrix; the calcium fluoride particles in existing technologies are mostly micron-sized (typically 0.3-2.5 μm in diameter), and there is a lack of systematic research on the dispersion technology and optimal addition scheme of nano-sized calcium fluoride in TPU. Summary of the Invention

[0008] (a) Technical problems to be solved The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a nano-calcium fluoride modified thermoplastic polyurethane battery separator and its preparation method. The aim is to utilize the multiple functions of nano-calcium fluoride (fluoride ion adsorption, in-situ generation of protective layer, mechanical enhancement, thermal stability and ion conduction promotion) to synergistically improve the overall performance of the battery. To solve the above-mentioned technical problems, the present invention adopts the following technical solution.

[0009] This invention provides a nano-calcium fluoride modified thermoplastic polyurethane battery separator, the battery separator comprising thermoplastic polyurethane (TPU) and nano-calcium fluoride, the nano-calcium fluoride being uniformly dispersed in the TPU matrix, the nano-calcium fluoride having a particle size of 10-500 nm, and the amount of nano-calcium fluoride added being 0.5-20 wt% based on the weight of the TPU.

[0010] As a preferred embodiment, the particle size of the nano-calcium fluoride is 20-200 nm, more preferably 50-100 nm.

[0011] As a preferred embodiment, the amount of nano-calcium fluoride added is 3-10 wt% based on the weight of TPU.

[0012] As a preferred embodiment, the nano-calcium fluoride undergoes surface modification treatment, and the surface modifier is selected from one or more of silane coupling agents, titanate coupling agents, aluminate coupling agents, polyvinylpyrrolidone, polyethylene glycol, sodium dodecyl sulfate, and hexadecyltrimethylammonium bromide.

[0013] As a preferred embodiment, the TPU is selected from polyester TPU, polyether TPU, polycarbonate TPU or mixtures thereof, and its number average molecular weight is 30,000-300,000.

[0014] As a preferred embodiment, the battery separator has a thickness of 5-150 μm, a porosity of 30%-80%, and an average pore size of 10-1000 nm.

[0015] The present invention also provides a method for preparing the above-mentioned nano-calcium fluoride modified thermoplastic polyurethane battery separator, comprising the following steps.

[0016] S1: Surface modification of nano-calcium fluoride. Nano-calcium fluoride powder is added to an organic solvent containing a surface modifier, ultrasonically dispersed for 30-120 minutes, and stirred at 50-90℃ for 1-6 hours. After centrifugation, washing, and drying, surface-modified nano-calcium fluoride is obtained. The organic solvent is selected from one or more of anhydrous ethanol, methanol, isopropanol, acetone, N-methylpyrrolidone, and N,N-dimethylformamide.

[0017] S2: Preparation of TPU solution. Thermoplastic polyurethane (TPU) particles are dissolved in an organic solvent and stirred at 40-90°C until completely dissolved, yielding a TPU solution with a mass concentration of 3%-30%. The organic solvent is selected from one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), tetrahydrofuran (THF), and dichloromethane (DCM).

[0018] S3: Dispersion of nano-calcium fluoride. The surface-modified nano-calcium fluoride obtained in step S1 is added to the TPU solution obtained in step S2, ultrasonically dispersed for 20-120 minutes, and then stirred at 500-5000 rpm for 0.5-5 hours to obtain a uniformly dispersed casting solution;

[0019] S4: Film Formation. The casting solution obtained in step S3 is used to form a film using a film-forming method. After drying, a nano-calcium fluoride modified TPU battery separator is obtained. The film-forming method is selected from one of solution casting, phase inversion, electrospinning, hot pressing, or coating. When using the phase inversion method, the casting solution is cast onto a substrate, controlling the wet film thickness to be 20-500 μm, and then immersed in a coagulation bath for phase inversion. The coagulation bath temperature is 0-60℃, the phase inversion time is 1-60 minutes, and finally, it is vacuum dried at 40-100℃ for 6-48 hours. The coagulation bath is selected from one or more of water, a mixture of water and an organic solvent, and an alcohol solvent. When using the electrospinning method, the casting solution is injected into an electrospinning device, and electrospinning is performed under the conditions of voltage 5-50 kV, receiving distance 5-30 cm, and spinning rate 0.1-5 mL / h to obtain a nanofiber membrane, which is then vacuum dried at 40-100℃ for 6-48 hours.

[0020] In this invention, the mechanism of action of nano-calcium fluoride in the TPU matrix mainly includes: nano-calcium fluoride has a high specific surface area and surface activity. There is a strong electrostatic interaction between the calcium ions (Ca²⁺) on its surface and the free fluoride ions (F⁻) in the electrolyte. This allows it to effectively capture free fluoride ions in the electrolyte through surface adsorption, stabilizing the chemical environment of the fluorinated electrolyte and thus inhibiting the corrosion of the positive and negative electrode materials by HF. Simultaneously, nano-calcium fluoride can undergo a cation exchange reaction with the harmful byproduct lithium carbonate (Li₂CO₃) in the electrolyte, generating lithium fluoride (LiF) and calcium carbonate (CaCO₃) in situ. The reaction formula is: CaF₂ + Li₂CO₃ → 2LiF + CaCO₃. LiF has high modulus and high interfacial stability, enabling the formation of a stable solid electrolyte interface, promoting dense deposition of lithium metal, and inhibiting the growth of lithium dendrites. In addition, nano-calcium fluoride, as an inorganic rigid filler, is uniformly dispersed in the TPU matrix, which can improve the tensile strength and puncture resistance of the membrane; nano-calcium fluoride has high thermal stability (melting point of about 1402-1423℃), which can inhibit the thermal shrinkage of TPU at high temperatures; the uniform distribution of nano-calcium fluoride particles in the TPU matrix can form additional ion transport channels in the matrix, thereby improving the ionic conductivity of the membrane. Compared with the prior art, the present invention has the following beneficial effects.

[0021] (1) This invention introduces nano-calcium fluoride into the TPU matrix, and utilizes its high specific surface area and the electrostatic adsorption of calcium ions on the surface to effectively capture free fluoride ions in the electrolyte, thereby inhibiting the generation and corrosion of HF from the source and extending the service life of the battery.

[0022] (2) Nano-calcium fluoride can undergo cation exchange reaction with harmful byproducts Li2CO3 in the electrolyte to generate high-modulus LiF and CaCO3 protective layers in situ, forming a stable SEI film, promoting dense deposition of lithium metal, effectively inhibiting the growth of lithium dendrites, and improving the safety performance of the battery.

[0023] (3) Nano-calcium fluoride, as an inorganic rigid filler, is uniformly dispersed in the TPU matrix, which can significantly improve the tensile strength, puncture resistance, and tear resistance of the membrane. Tests have shown that the tensile strength of the TPU membrane can be increased by 30%-80% after adding nano-calcium fluoride.

[0024] (4) Nano-calcium fluoride has high thermal stability, and its uniform dispersion in the TPU matrix can effectively inhibit the thermal shrinkage of TPU at high temperatures. Tests have shown that the thermal shrinkage rate of TPU membrane at 150℃ can be reduced from more than 35% to less than 15% after adding nano-calcium fluoride.

[0025] (5) The uniform distribution of nano-calcium fluoride particles in the TPU matrix can form additional ion transport channels in the matrix, while enhancing the wettability of the membrane to the electrolyte and improving the ionic conductivity of the membrane. Tests have shown that the ionic conductivity of the TPU membrane can be increased by 50%-150% after adding nano-calcium fluoride.

[0026] (6) The preparation process of the present invention is simple, requiring no complex coating equipment and additional binders, and is suitable for large-scale production. Attached Figure Description

[0027] Figure 1 The image shown is a scanning electron microscope (SEM) image of the TPU battery separator modified with nano-calcium fluoride prepared in Example 1 of the present invention, showing the dispersion state of the nano-calcium fluoride particles in the TPU matrix.

[0028] Figure 2 This is a comparison chart of the thermal shrinkage rates of the battery separators of Examples 1-5 and Comparative Example 1 at different temperatures (120°C, 150°C, 180°C).

[0029] Figure 3 This is a comparison diagram of the tensile strength of the battery separators in Examples 1-5 and Comparative Example 1 of the present invention.

[0030] Figure 4 The cycling performance curves (500 cycles) of the assembled button cells in Examples 1-5 and Comparative Example 1 of the present invention at a 1C rate.

[0031] Figure 5 This is a comparison chart of the ionic conductivity of the battery separators in Examples 1-5 and Comparative Example 1 of the present invention.

[0032] Figure 6This is a comparison chart showing the adsorption rates of fluoride ions (F⁻) in the electrolyte by the battery separators of Examples 1-5 and Comparative Example 1 of the present invention. Detailed Implementation

[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0034] In the following examples, the particle size of the nano-calcium fluoride used was determined by transmission electron microscopy (TEM) or scanning electron microscopy (SEM); the membrane thickness was determined by a thickness gauge; the porosity was determined by the liquid displacement method; the tensile strength was tested according to ASTM D882 standard; the thermal shrinkage rate was calculated by heating the membrane into 10cm×10cm samples at different temperatures for 1 hour; the ionic conductivity was determined by the AC impedance method; the fluoride ion adsorption rate was calculated by immersing the membrane in a LiPF6 electrolyte containing 50ppm F⁻ and placing it at 50°C for 72 hours, and then measuring the change in F⁻ concentration in the electrolyte; the battery cycle performance was tested using CR2032 coin cells assembled with LiFePO4 as the positive electrode, lithium metal as the negative electrode, and 1M LiPF6 in EC / EMC / DMC (volume ratio 1:1:1) as the electrolyte, and constant current charge-discharge tests were conducted at 25°C at a 1C rate, with a voltage range of 2.5-4.2V. Example 1

[0035] Step S1: Take 5g of nano-calcium fluoride powder with a particle size of 50-80nm, add it to 100mL of anhydrous ethanol, then add 0.5g of silane coupling agent KH-570, ultrasonically disperse for 45 minutes, and then stir and react at 70℃ for 3 hours. After the reaction, centrifuge, wash three times with anhydrous ethanol, and vacuum dry at 60℃ for 12 hours to obtain surface-modified nano-calcium fluoride. Step S2: Weigh 95 parts of thermoplastic polyurethane (polyether type TPU, number average molecular weight of about 120,000), add an appropriate amount of NMP solvent, stir and dissolve at 60℃ to obtain a TPU solution with a mass concentration of 12%. Step S3: Add 5 parts of the surface-modified nano-calcium fluoride obtained in Step S1 to the TPU solution obtained in Step S2, ultrasonically disperse for 60 minutes, and then stir at 2000rpm for 2 hours to obtain a casting solution. Step S4: The casting solution obtained in Step S3 is cast onto a clean glass plate. The wet film thickness is controlled to 200 μm using a doctor blade. Then, it is rapidly immersed in a deionized water coagulation bath at 25°C for phase inversion. After the film is completely cured, it is removed and thoroughly washed with deionized water to remove residual solvent. Finally, it is vacuum dried at 60°C for 24 hours to obtain a nano-calcium fluoride modified TPU battery separator. The obtained separator has a thickness of 42 μm, a porosity of 58%, and an average pore size of 85 nm. The separator exhibits a thermal shrinkage rate of 12.8% at 150°C, a tensile strength of 151.2 MPa, an ionic conductivity of 0.87 mS / cm, and an adsorption rate of fluoride ions in the electrolyte of 46%. After 500 cycles at 1C, the assembled coin cell retains 90.2% of its capacity. Example 2

[0036] The battery separator was prepared according to the method of Example 1, except that the amount of surface-modified nano-calcium fluoride and TPU added in step S3 was 3 parts. The resulting separator had a thickness of 41 μm, a porosity of 61%, and an average pore size of 92 nm. The separator exhibited a thermal shrinkage rate of 18.5% at 150°C, a tensile strength of 132.6 MPa, an ionic conductivity of 0.71 mS / cm, and an adsorption rate of 32% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 86.5% of its capacity. Example 3

[0037] The battery separator was prepared according to the method of Example 1, except that 8 parts of surface-modified nano-calcium fluoride and 92 parts of TPU were added in step S3. The resulting separator had a thickness of 43 μm, a porosity of 54%, and an average pore size of 78 nm. The separator exhibited a thermal shrinkage rate of 10.2% at 150°C, a tensile strength of 168.4 MPa, an ionic conductivity of 0.93 mS / cm, and an adsorption rate of 52% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 91.8% of its capacity. Example 4

[0038] The battery separator was prepared according to the method of Example 1, except that 10 parts of surface-modified nano-calcium fluoride and 90 parts of TPU were added in step S3. The resulting separator had a thickness of 44 μm, a porosity of 51%, and an average pore size of 72 nm. The separator exhibited a thermal shrinkage rate of 8.6% at 150°C, a tensile strength of 175.6 MPa, an ionic conductivity of 0.96 mS / cm, and an adsorption rate of 58% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 92.5% of its capacity. Example 5

[0039] The battery separator was prepared according to the method of Example 1, except that the amount of surface-modified nano-calcium fluoride and TPU added in step S3 was 1 part and 99 parts, respectively. The resulting separator had a thickness of 40 μm, a porosity of 63%, and an average pore size of 98 nm. The separator exhibited a thermal shrinkage rate of 28.4% at 150 °C, a tensile strength of 115.3 MPa, an ionic conductivity of 0.55 mS / cm, and an adsorption rate of 14% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 79.8% of its capacity. Example 6

[0040] The battery separator was prepared according to the method of Example 1, except that the particle size of the nano-calcium fluoride in step S1 was 20-40 nm. The resulting separator had a thickness of 41 μm, a porosity of 59%, and an average pore size of 68 nm. The separator exhibited a thermal shrinkage rate of 13.5% at 150 °C, a tensile strength of 148.7 MPa, an ionic conductivity of 0.89 mS / cm, and an adsorption rate of 49% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 89.8% of its capacity. Example 7

[0041] The battery separator was prepared according to the method of Example 1, except that the particle size of the nano-calcium fluoride in step S1 was 120-180 nm. The resulting separator had a thickness of 43 μm, a porosity of 56%, and an average pore size of 112 nm. The separator exhibited a thermal shrinkage rate of 14.2% at 150 °C, a tensile strength of 138.5 MPa, an ionic conductivity of 0.78 mS / cm, and an adsorption rate of 38% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 86.9% of its capacity. Example 8

[0042] The battery separator was prepared according to the method of Example 1, except that the surface modifier in step S1 was a titanate coupling agent (NDZ-101), used at 8% of the mass of the nano-calcium fluoride. The resulting separator had a thickness of 42 μm, a porosity of 57%, and an average pore size of 87 nm. The separator exhibited a thermal shrinkage rate of 13.1% at 150°C, a tensile strength of 149.8 MPa, an ionic conductivity of 0.85 mS / cm, and an adsorption rate of 45% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 89.5% of its capacity. Example 9

[0043] The battery separator was prepared according to the method of Example 1, except that the surface modifier in step S1 was polyvinylpyrrolidone (PVP, K30), and the amount used was 10% of the mass of the nano-calcium fluoride. The resulting separator had a thickness of 42 μm, a porosity of 59%, and an average pore size of 90 nm. The separator exhibited a thermal shrinkage rate of 13.8% at 150 °C, a tensile strength of 143.2 MPa, an ionic conductivity of 0.82 mS / cm, and an adsorption rate of 43% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 88.6% of its capacity. Example 10

[0044] The battery separator was prepared according to the method of Example 1, except that the TPU used in step S2 was polyester-type TPU (number-average molecular weight approximately 100,000). The resulting separator had a thickness of 43 μm, a porosity of 56%, and an average pore size of 83 nm. The separator exhibited a thermal shrinkage rate of 14.5% at 150°C, a tensile strength of 158.6 MPa, an ionic conductivity of 0.83 mS / cm, and an adsorption rate of 44% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 89.1% of its capacity. Example 11

[0045] The battery separator was prepared according to the method of Example 1, except that the TPU used in step S2 was polycarbonate-type TPU (number-average molecular weight approximately 150,000). The resulting separator had a thickness of 42 μm, a porosity of 57%, and an average pore size of 86 nm. The separator exhibited a thermal shrinkage rate of 11.8% at 150°C, a tensile strength of 162.3 MPa, an ionic conductivity of 0.84 mS / cm, and an adsorption rate of 45% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 89.7% of its capacity. Example 12

[0046] The battery separator was prepared according to the method of Example 1, except that the solvent in step S2 was DMF and the TPU solution had a mass concentration of 10%. The resulting separator had a thickness of 40 μm, a porosity of 62%, and an average pore size of 95 nm. The separator exhibited a thermal shrinkage rate of 13.2% at 150°C, a tensile strength of 146.5 MPa, an ionic conductivity of 0.86 mS / cm, and an adsorption rate of 44% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 89.3% of its capacity. Example 13

[0047] The battery separator was prepared according to the method in Example 1, except that the ultrasonic dispersion time in step S3 was 90 minutes and the stirring speed was 3000 rpm. The resulting separator had a thickness of 42 μm, a porosity of 59%, and an average pore size of 82 nm. The separator exhibited a thermal shrinkage rate of 12.5% ​​at 150°C, a tensile strength of 152.8 MPa, an ionic conductivity of 0.88 mS / cm, and an adsorption rate of 47% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 90.5% of its capacity. Example 14

[0048] The battery separator was prepared according to the method in Example 1, except that in step S4, electrospinning was used for film formation, with a spinning voltage of 20 kV, a receiving distance of 15 cm, and a spinning rate of 1 mL / h. The resulting separator had a thickness of 35 μm, a porosity of 68%, and an average pore size of 150 nm. The separator exhibited a thermal shrinkage rate of 15.6% at 150 °C, a tensile strength of 98.4 MPa, an ionic conductivity of 0.92 mS / cm, and an adsorption rate of 42% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 87.2% of its capacity. Example 15

[0049] The battery separator was prepared according to the method of Example 1, except that in step S4, solution casting was used to form the film, which was then dried at 80°C for 48 hours. The resulting separator had a thickness of 45 μm, a porosity of 35%, and an average pore size of 45 nm. The separator exhibited a thermal shrinkage rate of 11.2% at 150°C, a tensile strength of 175.3 MPa, an ionic conductivity of 0.52 mS / cm, and an adsorption rate of 48% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 85.6% of its capacity. Example 16

[0050] The battery separator was prepared according to the method of Example 1, except that the coagulation bath temperature in step S4 was 10°C. The resulting separator had a thickness of 44 μm, a porosity of 52%, and an average pore size of 72 nm. The separator exhibited a thermal shrinkage rate of 13.6% at 150°C, a tensile strength of 155.8 MPa, an ionic conductivity of 0.81 mS / cm, and an adsorption rate of 46% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 89.8% of its capacity. Example 17

[0051] The battery separator was prepared according to the method of Example 1, except that the coagulation bath temperature in step S4 was 40°C. The resulting separator had a thickness of 39 μm, a porosity of 65%, and an average pore size of 105 nm. The separator exhibited a thermal shrinkage rate of 14.5% at 150°C, a tensile strength of 132.4 MPa, an ionic conductivity of 0.90 mS / cm, and an adsorption rate of 43% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 88.1% of its capacity. Example 18

[0052] The battery separator was prepared according to the method of Example 1, except that the surface modifier in step S1 was a silane coupling agent KH-550 (γ-aminopropyltriethoxysilane). The resulting separator had a thickness of 42 μm, a porosity of 58%, and an average pore size of 86 nm. The separator exhibited a thermal shrinkage rate of 13.0% at 150°C, a tensile strength of 150.5 MPa, an ionic conductivity of 0.86 mS / cm, and an adsorption rate of 46% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 90.0% of its capacity. Example 19

[0053] The battery separator was prepared according to the method of Example 1, except that the surface modifier in step S1 was a silane coupling agent KH-560 (γ-glycidoxypropyltrimethoxysilane). The resulting separator had a thickness of 42 μm, a porosity of 58%, and an average pore size of 88 nm. The separator exhibited a thermal shrinkage rate of 13.3% at 150 °C, a tensile strength of 147.9 MPa, an ionic conductivity of 0.84 mS / cm, and an adsorption rate of 44% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 89.2% of its capacity. Example 20

[0054] The battery separator was prepared according to the method of Example 1, with the difference that the amount of nano-calcium fluoride added in step S3 was 12 parts and TPU was 88 parts. The resulting separator had a thickness of 45 μm, a porosity of 48%, and an average pore size of 65 nm. The separator had a thermal shrinkage rate of 7.8% at 150°C, a tensile strength of 182.5 MPa, an ionic conductivity of 0.98 mS / cm, and an adsorption rate of fluoride ions in the electrolyte of 62%. After 500 cycles at 1C, the assembled coin cell retained 92.8% of its capacity. When the amount of nano-calcium fluoride added exceeded 10 parts, slight agglomeration of the particles occurred in the TPU matrix, which had a certain impact on the uniformity and flexibility of the separator. Compare with Example 1

[0055] The battery separator was prepared according to the method in Example 1, except that no nano-calcium fluoride was added; only TPU (100 parts) was used to prepare the separator. The resulting separator had a thickness of 40 μm, a porosity of 64%, and an average pore size of 105 nm. The separator exhibited a thermal shrinkage rate of 38.2% at 150°C, a tensile strength of 102.3 MPa, an ionic conductivity of 0.42 mS / cm, and an adsorption rate of 8% for fluoride ions in the electrolyte. After 500 cycles at 1C, the capacity retention of the assembled coin cell was only 68.7%. Compare with Example 2

[0056] The battery separator was prepared according to the method in Example 1, except that the added nano-calcium fluoride was not surface-modified. The resulting separator had a thickness of 43 μm, a porosity of 51%, an average pore size of 120 nm, and exhibited significant agglomeration. The separator showed a thermal shrinkage rate of 22.6% at 150 °C, a tensile strength of 118.5 MPa, an ionic conductivity of 0.58 mS / cm, and an adsorption rate of 28% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 78.3% of its capacity. This indicates that the unmodified nano-calcium fluoride was unevenly dispersed in TPU, affecting the overall performance improvement. Compare with Example 3

[0057] The battery separator was prepared according to the method in Example 1, except that the added calcium fluoride was micron-sized (particle size 1.5-2.5 μm). The resulting separator had a thickness of 44 μm, a porosity of 50%, and an average pore size of 185 nm. The separator exhibited a thermal shrinkage rate of 25.8% at 150 °C, a tensile strength of 108.7 MPa, an ionic conductivity of 0.48 mS / cm, and an adsorption rate of 18% for fluoride ions in the electrolyte. After 500 cycles at 1C, the assembled coin cell retained 75.6% of its capacity. This indicates that the specific surface area of ​​micron-sized calcium fluoride is insufficient, and its fluoride ion adsorption and enhancement effects are significantly lower than those of nano-sized calcium fluoride.

Claims

1. A nano-calcium fluoride modified thermoplastic polyurethane battery separator, characterized in that, The battery separator comprises thermoplastic polyurethane and nano-calcium fluoride. The nano-calcium fluoride is uniformly dispersed in the thermoplastic polyurethane matrix. The particle size of the nano-calcium fluoride is 10-500 nm. The amount of nano-calcium fluoride added is 0.5-20 wt% based on the weight of the thermoplastic polyurethane.

2. The nano-calcium fluoride modified thermoplastic polyurethane battery separator according to claim 1, characterized in that, The nano-calcium fluoride has a particle size of 20-200 nm, and the amount of nano-calcium fluoride added is 3-10 wt% based on the weight of thermoplastic polyurethane.

3. The nano-calcium fluoride modified thermoplastic polyurethane battery separator according to claim 1, characterized in that, The nano-calcium fluoride undergoes surface modification treatment, and the surface modifier is selected from one or more of silane coupling agents, titanate coupling agents, aluminate coupling agents, polyvinylpyrrolidone, polyethylene glycol, sodium dodecyl sulfate, and hexadecyltrimethylammonium bromide.

4. The nano-calcium fluoride modified thermoplastic polyurethane battery separator according to claim 1, characterized in that, The thermoplastic polyurethane is selected from polyester-type thermoplastic polyurethane, polyether-type thermoplastic polyurethane, polycarbonate-type thermoplastic polyurethane, or mixtures thereof, and its number average molecular weight is 30,000-300,000.

5. The nano-calcium fluoride modified thermoplastic polyurethane battery separator according to claim 1, characterized in that, The battery separator has a thickness of 5-150 μm, a porosity of 30%-80%, and an average pore size of 10-1000 nm.

6. A method for preparing a nano-calcium fluoride modified thermoplastic polyurethane battery separator according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1: Add nano-calcium fluoride powder to an organic solvent containing a surface modifier, ultrasonically disperse for 30-120 minutes, stir at 50-90℃ for 1-6 hours, centrifuge, wash, and dry to obtain surface-modified nano-calcium fluoride; S2: Dissolve thermoplastic polyurethane particles in an organic solvent, stir at 40-90℃ until completely dissolved to obtain a thermoplastic polyurethane solution with a mass concentration of 3%-30%; S3: Add the surface-modified nano-calcium fluoride obtained in step S1 to the thermoplastic polyurethane solution obtained in step S2, ultrasonically disperse for 20-120 minutes, and then stir at 500-5000 rpm for 0.5-5 hours to obtain a casting solution; S4: The casting solution obtained in step S3 is used to prepare a film by a film-forming method, and after drying, a nano-calcium fluoride modified thermoplastic polyurethane battery separator is obtained.

7. The preparation method according to claim 6, characterized in that, The organic solvent in step S1 is selected from one or more of anhydrous ethanol, methanol, isopropanol, acetone, N-methylpyrrolidone, and N,N-dimethylformamide; the organic solvent in step S2 is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, and dichloromethane.

8. The preparation method according to claim 6, characterized in that, The film-forming method described in step S4 is selected from one of the following: solution casting, phase inversion, electrospinning, hot pressing, or coating.

9. The preparation method according to claim 8, characterized in that, When using the phase inversion method, the casting solution is cast onto a substrate, and the wet film thickness is controlled to be 20-500 μm. Then, it is immersed in a coagulation bath for phase inversion. The coagulation bath temperature is 0-60℃, and the phase inversion time is 1-60 minutes. Finally, it is vacuum dried at 40-100℃ for 6-48 hours. The coagulation bath is selected from one or more of water, a mixture of water and organic solvent, and alcohol solvent. When using the electrospinning method, the casting solution is injected into an electrospinning device, and electrospinning is performed under the conditions of voltage 5-50 kV, receiving distance 5-30 cm, and spinning rate 0.1-5 mL / h to obtain a nanofiber membrane, which is then vacuum dried at 40-100℃ for 6-48 hours.

10. The application of the nano-calcium fluoride modified thermoplastic polyurethane battery separator according to any one of claims 1 to 5 in lithium-ion batteries or lithium metal batteries.

Citation Information

Patent Citations

  • Composite diaphragm, preparation method and application

    CN120767538A